Deformation localization and crack propagation of sandstone containing different flaw inclination angles under different loading rates - Li, Chengjin; Pan, Lin; Zhang, Liwei; Chris A., Mary; Galang, Alma G. (Frontiers in Earth Science, 2023)
Defects with varying geometric distribution in the rock mass play a crucial role in determining the stability of engineered rock masses. Previous studies have primarily investigated the initiation, propagation, and coalescence behaviors of flaws within rock masses. Nevertheless, there has been limited analysis of flawed rock masses under different loading rates. In this study, we present the deformation localization and cracking process of three types of inclined flawed sandstone specimens through conducting uniaxial compression and acoustic emission tests at four different levels of loading rate. The results supported the following findings: (1) Sandstone specimens with different flaw inclination angles exhibit the loading rate strengthening effect, and the strengthening effect gradually decreases with the increase of loading rate. (2) As the loading rate increases, the type of crack emergence changes from wing cracks to anti-tensile cracks, and the time of flaw initiation is shortened. (3) The cumulative acoustic emission counts were higher for the low-loading rate specimens than for the high-loading rate specimens. ( 4) Tensile cracks typically occur as the initial cracks. Anti-tensile cracks often coexist with wing cracks in rock specimens that have undergone tensile damage. Coplanar secondary cracks are the primary indication of shear damage formation in rock specimens. (5) The increase in loading rate promotes the transition of rock specimens from the mixed tensile-shear damage mode to the shear damage mode. These research results are of great theoretical significance and engineering value for understanding the failure mechanism of rock mass containing flaws and proposing effective measures to prevent cracking and ensure the safety of brittle solid structures.